Assessing the potential production of uranium from coal-ash milling in the long term. (September 2015) - Monnet, Antoine; Percebois, Jacques; Gabriel, Sophie
Abstract: Uranium-bearing coal deposits are occasionally mentioned as a potential source of supply for nuclear fuels. The production of uranium from coal-ash has remained sub-economic for decades, but the emergence of new projects has once again raised a number of questions. How much coal-ash do we have? Are the coal deposits all rich in uranium? Can the uranium content always be recovered? This study shows that there are significant quantities of uranium in the ash produced by the world coal consumption: between 7 ktU and 13 ktU in 2012. Yet, most of this ash correspond to very low grade ores and potential production capacities should not exceed 700 tU/yr in today's economic conditions (between 40 and 70 /lbU3 O8 for both spot and long-term price over the period 2011–2014 (Ux Consulting, 2015 )), i.e. approximately 1% of current needs. On the long-term, the sensitivity of the production potential to economic factors (cut-off grade, uranium price) and coal-consumption scenarios is moderate. Economic production from coal-ash should not exceed a couple of percents of uranium needs. Highlights: Most coals have very low uranium grade but lignite may prove better than average. 7 to 13 ktU are contained in the coal-ash produced by the energy sector in 2012. In the price range of 40–70 /lbU3 08, a maximum of 700 tU/yr could be marketable. On the long term, this potential production could vary around 1% of needs. The world trend for this uranium potential is shaped by non-OECD countries.